The impact of income inequality on economic growth - Petersen, Thiess; Schoof, Ulrich (Gütersloh, 2015)
"Increases in income inequality have both growth-promoting effects (stronger performance incentives, as well as incentives to invest in one’s own human capital, to take risks, and to make investments) and growth-dampening effects (demotivating incentives, social tensions and political unrest, declines in demand as a brake on growth). While increases in income inequality in the 1950s and the 1960s still led to growth-promoting effects, current studies increasingly identify growth-dampening effects. Particularly in highly developed economies such as Germany, Japan and the United States, these studies indicate that increasing income inequality has reached a level that is becoming a brake on growth. For this reason, there is no fundamental contradiction between state-led income redistribution and economic growth. The reduction of income inequality should not be limited to a pure redistribution through the tax-transfer system, but should also include a rebalancing of the supply-side policies of the past 30 years."